Relationship to victim predicts sentence length in sexual assault cases - Seto, Michael C.; Barbaree, H. E.; MacCormick, Jennifer S.; Maric, Alexandra (Journal of interpersonal violence, 1998)
There is good evidence that rapists and rape are viewed differently according to the social relationship between the victim and offender. Clinical files from 204 rapists incarcerated at a medium-security penitentiary were reviewed. The rapists were divided into three groups: 103 stranger rapists, 36 acquaintance rapists, and 65 partner rapists (including 20 men who sexually assaulted ex-partners). Based on previous findings, we predicted no group differences in terms of demographic or offense characteristics. Based on social psychological and legal findings, we predicted that victim-offender relationship would be related to sentence length, even after controlling for presumably relevant factors such as the offender's criminal history. Our predictions were supported. Stranger rapists used more force that partner rapists and caused more physical injury than rapists of known victims. However, these factors did not predict sentence length. There were only two significant predictors: excessiveness of force used and victim-offender relationship